Disentangling the effects of parental food restriction on child's risk of overweight. (1st April 2018) - Godefroy, Valérie; Champel, Camille; Trinchera, Laura; Rigal, Natalie
Abstract: The links between parental restriction of food intake, child's eating behaviour and child's adiposity are still unclear. Our aim was to validate a model suggesting an underlying mechanism for the impact of parental restriction on child's adiposity through a broad dimension of child's eating temperament entitled the appetite reactivity (including both appetite arousal and appetite persistence). Using an online questionnaire administered at home to children aged between 8 and 11 years ( N  = 414) with one or both of their parents, we measured: based on child's reports, the perceived maternal restriction of child's food intake, the appetite reactivity and both the desired and the eaten mean food portion sizes; based on parental reports, the mean food portion size given to the child and the child's BMI. Structural equation modelling was used to test a model linking measured variables. A well-fitting structural model (AGFI = 0.91; RMSEA = 0.07; SRMR = 0.08) was identified, showing that: (i) perceived maternal restriction of child's food intake negatively impacts child's appetite arousal and food portion size but positively influences child's appetite persistence; (ii) the two components of appetite reactivity have a positive effect on child's adiposity which is partly mediated by child's actual food portion size. Results suggest an explanation for the controversy surrounding the links between parental food restriction and child's adiposity: through its negative impact on child's appetite arousal and food portion size, parental control may protect against overweight, but because of its positive effect on appetite persistence, it can also be detrimental.